Konsep Paradoks: Kedaulatan Allah dan Kebebasan Manusia Menurut Perspektif Teologi Reformed [A Paradoxical Concept: God's Sovereignty and Human Freedom According to a Reformed Theological Perspective] - Zega, Sri Susianti (Diligentia: Journal of Theology and Christian Education, 2023)
Humans can only understand salvation through God's revelation in the Bible. The Bible teaches that the matter of salvation is both God's sovereignty and man's inseparable responsibility, which is understood as a paradoxical concept. But in reality, 6 out of 11 Christian students do not understand the paradoxical truth about salvation taught by the Bible according to a randomly distributed survey. Christian students who have accepted theological doctrines should understand the paradoxical truth about salvation. An important aim of writing this essay is to show the understanding of Reformed theology (represented by John Calvin, Louis Berkhof, Anthony Hoekema, and J.I. Packer) regarding salvation as God's sovereignty and human responsibility using literary sources. Reformed theologians (Calvin, Berkhof, Hoekema, and Packer) accepted the paradoxical concept and believed that humans contribute to the regeneration of identity through God's grace. God's grace is the main reason humans can obey this. Therefore, understanding the concept of paradoxical truth must be accompanied by love and humility before God.BAHASA INDONESIA ABSTRACT: Manusia hanya dapat memahami keselamatan melalui wahyu Allah melalui Alkitab. Alkitab mengajarkan bahwa mengusahakan keselamatan adalah kedaulatan Tuhan dan tanggung jawab manusia yang tidak terpisahkan, yang dipahami sebagai konsep paradoks. Namun pada kenyataannya, 6 dari 11 mahasiswa Kristen tidak memahami kebenaran paradoksal tentang keselamatan yang diajarkan oleh Alkitab, berdasarkan survei yang disebarkan secara acak. Mahasiswa Kristen yang telah menerima doktrin teologi seharusnya memahami kebenaran paradoksal tentang mengerjakan keselamatan. Tujuan penting dari penulisan esai ini adalah untuk menunjukkan pemahaman teologi Reformed (yang diwakili oleh John Calvin, Louis Berkhof, Anthony Hoekema, dan Packer) mengenai keselamatan sebagai kedaulatan Allah dan tanggung jawab manusia atas keselamatan dengan menggunakan sumber-sumber literatur. Konsep paradoksal dalam mengerjakan keselamatan sebagai kedaulatan Allah dan tanggung jawab manusia. Kebenaran yang diajarkan oleh Alkitab, para teolog Reformed (Calvin, Berkhof, Hoekema, dan Packer) menerima konsep paradoksal dan percaya bahwa manusia berkontribusi dalam regenerasi identitas melalui kasih karunia Allah. Kasih karunia Allah sebagai penyebab utama manusia dapat taat mengerjakan keselamatan. Oleh karena itu, memahami konsep kebenaran paradoksal harus disertai dengan kasih dan kerendahan hati di hadapan Tuhan.